The - Greshes, Warren
The Best Damn Management Book Ever teaches managers, executives, and business owners how to create a staff of self-motivated, confident, high-achieving, self-starters. Acclaimed author of The Best Damn Sales Book Ever, Warren Greshes draws from years of experience to offer practical, easy-to-implement steps explained through entertaining, informative real-life stories